2015
DOI: 10.1016/j.matdes.2015.07.084
|View full text |Cite
|
Sign up to set email alerts
|

High temperature tensile deformation behavior and failure mechanisms of an Al–Si–Cu–Mg cast alloy — The microstructural scale effect

Abstract: In this study the high temperature tensile deformation behavior of a commercial Al-Si-Cu-Mg cast alloy was investigated. The alloy was cast with two different cooling rates resulted in average secondary dendrite arm spacing of 10 and 25 μm, which are typical of the microstructure scale obtained from high pressure die casting and gravity die casting. Tensile tests were performed at different strain rates (10 -4 s -1 to 10 -1 s -1 ) and over a wide temperature range from ambient temperature to 500 ºC. The fine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…Han et al [12] suggested different dissolution rates for eutectic Al 2 Cu and block-like Al 2 Cu phase where the former dissolves by fragmentation to smaller parts and eventually dissolves by radial diffusion of Cu in the matrix, while the latter dissolves by spheroidisation and shrinkage. The author pointed out in another work that size and morphology of Al 2 Cu phase influence dissolution rate where fine particles with lower aspect ratio dissolve faster than coarse elongated one [13]. In the present study, the comparison between the dissolution rates of Al 2 Cu for different microstructural scales from their three microstructural scales is not straightforward where the fast solidification rate resulted in dendritic growth of a-Al, while two slower solidification rates resulted in cellular growth (Fig.…”
Section: Alloysmentioning
confidence: 60%
See 3 more Smart Citations
“…Han et al [12] suggested different dissolution rates for eutectic Al 2 Cu and block-like Al 2 Cu phase where the former dissolves by fragmentation to smaller parts and eventually dissolves by radial diffusion of Cu in the matrix, while the latter dissolves by spheroidisation and shrinkage. The author pointed out in another work that size and morphology of Al 2 Cu phase influence dissolution rate where fine particles with lower aspect ratio dissolve faster than coarse elongated one [13]. In the present study, the comparison between the dissolution rates of Al 2 Cu for different microstructural scales from their three microstructural scales is not straightforward where the fast solidification rate resulted in dendritic growth of a-Al, while two slower solidification rates resulted in cellular growth (Fig.…”
Section: Alloysmentioning
confidence: 60%
“…The melt was gravity-die-casted in a 250°C preheated copper die having six cylindrical fingers of 200 mm long and 10 mm diameter. The cast rods were then re-melted at 730°C for 30 min under Ar atmosphere in a Bridgman furnace and then directionally solidified [13]. The furnace was mounted on a motorised lifting device, while the rods are in a stationary position.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of Cu and Mg to Al-Si alloys was reported to promote their mechanical properties through the precipitation of the Al 2 Cu, Mg 2 Si phases [5][6][7][8]. Furthermore, it was reported that Ni is a desirable element for improving the mechanical properties of Al-Si-based alloys at elevated temperatures by forming thermally stable Ni-containing intermetallics [9].…”
Section: Introductionmentioning
confidence: 99%